2011
DOI: 10.1111/j.1547-5069.2011.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genomics Into Undergraduate Nursing Education

Abstract: To provide information that may assist faculty to prepare the next generation of nurses to practice using genomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…[9,10] Studies exploring perceived genetic knowledge and teaching strategies related to the inclusion of genetic content into curricula has been conducted in the United Kingdom; [11,12] New Zealand; [13] Japan; [14] Turkey; [15] Taiwan; [16] and the United States. [7,8,[17][18][19][20][21] These studies revealed that perceived genetic knowledge and clinical comfort remain inadequate among pre-licensure nursing students or advanced practice nursing students. [16] Studies exploring nurse faculty members' perceived knowledge of genetics continue to demonstrate the limitation of faculty to teach this content.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] Studies exploring perceived genetic knowledge and teaching strategies related to the inclusion of genetic content into curricula has been conducted in the United Kingdom; [11,12] New Zealand; [13] Japan; [14] Turkey; [15] Taiwan; [16] and the United States. [7,8,[17][18][19][20][21] These studies revealed that perceived genetic knowledge and clinical comfort remain inadequate among pre-licensure nursing students or advanced practice nursing students. [16] Studies exploring nurse faculty members' perceived knowledge of genetics continue to demonstrate the limitation of faculty to teach this content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[27,28] This instrument, initially developed to evaluate genetic education in undergraduate nonscience majors, has been utilized in nursing studies and has been validated as a reliable assessment of nursing students' and faculty's knowledge of genetic concepts, providing accurate assessment of foundational genetic/genomic knowledge. [8,20] The GLAI, a 31-item multiple choice survey assessing 17 subconcepts organized around six larger domains: nature of genetic material; transmission; gene expression; gene regulation; evolution; and genetics and society, providing a wellgrounded level of perceived knowledge of genetics/genomics concepts correlating to the nursing professions' concepts. In addition to the GLAI, participants were asked to complete three demographic questions (grade level, gender and age) as well as two questions to explore students' perceived comfort level: How comfortable in collecting a patients' family history/drawing/analyzing a three-generation pedigree and how comfortable in explaining the various Mendelian inheritance patterns to patients (such as autosomal dominant, autosomal recessive, X-linked disorders and mitochondrial disorders).…”
Section: Methodsmentioning
confidence: 99%
“…[17] The gap between faculty knowledge and integration of genetic and genomic content in curricula continues today. [18] Yet for nursing faculty to educate their students, they first must educate themselves. There are several exceptional genetic education programs geared towards the healthcare professional.…”
Section: Competency Of Nurse Educators To Educatementioning
confidence: 99%
“…The self-study was followed up with a 1-day, on-site consultation by the nurse expert who provided background and significance for the need to integrate genomics into the curriculum, examples of how and where to place genomics into the curriculum based on the self-study, and teaching and learning resources for faculty (Daack-Hirsch et al, 2013). This process can be used at the undergraduate and graduate levels and lead to threading omics across the curriculum, addressing it in a series of courses, developing a specific course, or a combination of these approaches (Daack-Hirsch et al, 2011 andDaack-Hirsch et al, 2013). Additionally, some schools of nursing do currently have training programs for PhD students in the omics.…”
mentioning
confidence: 99%